Pelatihan Pemanfaatan Teknologi Google Drive dan Blogs bagi Pengawas Sekolah Dasar - Erpidawati; Novelti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
In the world of education, we must quickly obtain information and be fast in sending the requested information. Indonesia is one of the developing countries that is trying to take advantage of this digitization system. With the digitization system, it is hoped that it will make it easier to send and convey information to relevant agencies in need. This activity is carried out with the aim of providing training and technical implementation so that school supervisors can take advantage of supporting media and provide useful new knowledge. The method used in this community service is the seminar method. The results obtained after this activity were that the participants were able to apply google drive and create blogs independently, in turn, and under supervision. The conclusion of the research results is that school supervisors get new knowledge, are able to operate and create google drives and blogs, understand that adding data storage patterns and data management can be done easily and efficiently.